623 Immuno-STATs: Leveraging protein engineering to expand and track antigen-specific T cells in vivo. (9th November 2020) - Zeigler, Stad; Woodham, Andrew; Li, Mengyan; Zeyang, Ella; Kolifrath, Stephen; Rashidian, Mohammad; O'Connor, Kaitlyn; Chaparro, Rodolfo; Seidel, Ronald; Mesyngier, Maia; Cheloha, Ross; Dearling, Jason; et al.
Abstract : Background: Immunotherapies are highly promising and effective strategies for the treatment of cancer; however, continuing challenges persist, including 1) untargeted global immune modulation, resulting in serious side effects; 2) lack of therapeutics capable of in vivo expansion of tumor-specific T cells; 3) inability to visualize in vivo tumor-specific T cell responses; and 4) lack of flexible platforms to rapidly and efficiently explore new therapeutic strategies and immune-escape mechanisms. To address these challenges, we developed a novel class of precision biologics to treat cancer, autoimmune diseases and infectious diseases. We describe a modular platform constructed around an Fc-based covalent pMHC dimer, referred to as synTac (artificial synapse for T cell activation; also termed Immuno-STATs for Selective Targeting and Alteration of T cells), which selectively delivers different cargoes, including costimulatory, coinhibitory or cytokine signals and other modalities to primary T cells of defined specificity. The inherent modularity supports broad applications. Changing the encoded peptide enables targeting of different T cell specificities to address different diseases, while altering the cargo allows for evaluation of different co-modulatory mechanisms or the delivery of mechanistically informative probes. Methods: Sortase A-mediated enzymatic coupling supported site-specific and stoichiometric installation of positron emission tomography (PET)-active radiolabels on synTacs to visualize the in vivo localization of antigen-specific T cells. The NSG humanized mouse model allowed for the evaluation of synTacs/Immuno-STATs to drive the in vivo antigen-specific expansion of human CD8 T cells. Results: Using radiolabeled synTacs/Immuno-STATs loaded with the appropriate peptides, we employed positron emission tomography to localize human papillomavirus (HPV16)-specific CD8 T cells to implanted HPV16-positive tumors in mice, as well as influenza A virus (IAV)-specific CD8 T cells in the lungs of IAV-infected mice. In vivo administration of HIV- and CMV-specific synTacs/Immuno-STATs to immunodeficient mice intrasplenically engrafted with human donor PBMCs resulted in the marked and selective expansion of HIV-specific and CMV-specific human CD8 T cells populating their spleens, respectively. Conclusions: We demonstrate the remarkable flexibility of the synTacs/Immuno-STAT platform for addressing a broad range of applications, including the first report of the in vivo imaging of antigen-specific CD8 T cell populations and in vivo antigen-selective expansion of human CD8 T cells. These results suggest that, in addition to broad therapeutic applications, synTac/Immuno-STATs may provide prognostic/diagnostic information. Most notably, these results demonstrate the presence of synTacs/Immuno-STAT biologics in the tumor or infected tissues where they can elicit T cell restimulation and expansion necessary for target killing and enhanced therapeutic efficacy.